COVID‐19 guidelines for pregnant women and new mothers: A systematic evidence review. Issue 3 (29th March 2021) - DiLorenzo, Madeline A.; O'Connor, Sarah K.; Ezekwesili, Caroline; Sampath, Spoorthi; Zhao, Molly; Yarrington, Christina; Pierre, Cassandra
Abstract: Background: Nearly a year after COVID‐19 was initially detected, guidance for pregnant and new mothers remains varied. Objective: The goal of this systematic review is to summarize recommendations for three areas of maternal and fetal care—breastfeeding, post‐partum social distancing, and decontamination. Search strategy: We searched PubMed, Embase and Web of Science spanning from inception to November 9, 2020. Selection criteria: Articles were included if they focused on COVID‐positive mothers, commented on at least one of the three areas of interest, and were published in English. Data collection and analysis: Our combined database search yielded 385 articles. After removing duplicates and articles that did not cover the correct populations or subject matter, a total of 74 articles remained in our analysis. Main results: Most articles recommended direct breastfeeding with enhanced precaution measures. Recommendations regarding post‐partum social distancing varied, although articles published more recently often recommended keeping the mother and newborn in the same room when possible. Decontamination recommendations emphasized mask wearing, good hand hygiene, and proper cleaning of surfaces. Conclusion: In general, there was a focus on shared decision making when approaching topics such as breastfeeding and post‐partum social distancing. Guidelines for decontamination were fairly uniform. Synopsis: Breastfeeding with enhanced precautions was often recommended. Post‐partum social distancing recommendations emphasized shared decision making. Decontamination focused on masks, hand hygiene, and proper surface cleaning.